2013
DOI: 10.1016/j.medin.2012.12.013
|View full text |Cite
|
Sign up to set email alerts
|

2013. Documento Sevilla de Consenso sobre Alternativas a la Transfusión de Sangre Alogénica. Actualización del Documento Sevilla

Abstract: Since allogeneic blood transfusion (ABT) is not harmless, multiple alternatives to ABT (AABT) have emerged, though there is great variability in their indications and appropriate use. This variability results from the interaction of a number of factors, including the specialty of the physician, knowledge and preferences, the degree of anemia, transfusion policy, and AABT availability. Since AABTs are not harmless and may not meet cost-effectiveness criteria, such variability is unacceptable. The Spanish Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 202 publications
0
12
0
9
Order By: Relevance
“…6 The use of intravenous iron is the most effective way to prevent iron deficiency associated with IBD. 75 Data from randomised studies have shown that the use of intravenous iron is effective for replenishment of iron and prevention of IBD-associated anaemia. [76][77][78] Iron sucrose and iron carboxymaltose are also effective in the replenishment of iron, but iron carboxymaltose shown higher efficacy.…”
Section: Rationalementioning
confidence: 99%
“…6 The use of intravenous iron is the most effective way to prevent iron deficiency associated with IBD. 75 Data from randomised studies have shown that the use of intravenous iron is effective for replenishment of iron and prevention of IBD-associated anaemia. [76][77][78] Iron sucrose and iron carboxymaltose are also effective in the replenishment of iron, but iron carboxymaltose shown higher efficacy.…”
Section: Rationalementioning
confidence: 99%
“…La mayoría de estos expertos habían participado en la elaboración de la Actualización del Documento Sevilla 2013 (DS2013), avalada por 6 sociedades científicas de ámbito nacional 10 , aunque en esta ocasión actuaban a título personal y no en representación de sus respectivas sociedades.…”
Section: Metodologíaunclassified
“…Sin embargo, han llevado a cambios en sus indicaciones y pautas de tratamiento en enfermos renales y oncológicos 16,17 . En el contexto quirúrgico, la eritropoyetina humana recombinante (epoetina alfa, rHuEPO) solamente tiene indicación en pacientes de cirugía ortopédica programada con Hb o para facilitar la donación autógena preoperatoria, aunque se ha utilizado en cirugía traumatológica, cardíaca y oncológica 10 . En la indicación aprobada, 2 estudios en cirugía vertebral han reportado un aumento de trombosis venosa en pacientes tratados con rHuEPO y que no recibieron tromboprofilaxis 7,8 .…”
Section: Agentes Estimuladores De La Eritropoyesis Antecedentesunclassified
See 2 more Smart Citations